THE USE OF TRANSFORMATION DRILL TECHNIQUE TO IMPROVE STUDENTS’ ABILITY IN SIMPLE PRESENT TENSE TO THE SECOND YEAR STUDENT OF SMA NEGERI 1 TENGA - Yosia Liow; Sanerita T. Olii; Rinny Rorimpandey (Program Studi Pendidikan Bahasa Inggris, 2022)
This research was conducted to the eleven grade student especially in science class of SMA Negeri 1 Tenga in the academic year of 2021-2022 odd semester. There were 28 students chosen as the sample of this research. To fulfil the purpose of the research, the researcher took experimental research involved one class to be given treatment. The data were obtained through pre-test and post-test. The hypothesis of this research indicated that there was a significant difference between the score of the pre-test and post-test. The score of the post-test got higher than the pre-test. The mean score of pre- test was 62.21 and the mean score of post-test was 79.25. Based on the results, the researcher concluded that teaching simple present tense by using transformation drill technique was effective because it can improve students’ ability in making simple present tense sentences correctly. And these techniques are appropriate to be applied.